In justice - Iglesias, David (John Wiley & Sons, 2008)
The Bush administration's drive to politicize the Justice Department reached a new low with the wrongful firing of seven U.S. Attorneys in late 2006. Their action has ignited public outrage on a scale that far surpassed the reaction to any of the Bush administration's other political debacles. David Iglesias was one of those federal prosecutors, and now he tells his story